Updating warning systems for climate hazards: Can navigation satellites help? - Handmer, John; Choy, Suelynn; Kohtake, Naohiko (Journal of Telecommunications and the Digital Economy, 2020)
Warning systems are relied on worldwide as part of disaster risk reduction. The traditional model of a government monopolistic system supplying warnings through a broadcast approach is now challenged by new media, mobile technologies and the accompanying expectations of individualised warnings to personal mobile devices. We examine this situation, and one novel approach – the use of an augmented signal from the next generation of Japanese positioning satellites – to providing individual warnings to personal devices wherever their owners are. We conclude that delivery to personal devices is feasible and already happening to some extent. Linking these new official systems with the multiple information flows of social media and crowdsourcing remains a major challenge.